2007
DOI: 10.1111/j.1540-5834.2007.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Abstract

Abstract: Despite the importance of learning abilities and disabilities in education and child development, little is known about their genetic and environmental origins in the early school years. We report results for English (which includes reading, writing, and speaking), mathematics, and science as well as general cognitive ability in a large and representative sample of U.K. twins studied at 7, 9, and 10 years of age. Although preliminary reports of some of these data have been published, the purpose of this monogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 93 publications
2
14
0
Order By: Relevance
“…The finding that the heritability of high performance in adolescents, for both ART and reading and spelling ability, is of similar magnitude to that found in the population sample, is in line with previous reports for high general cognitive abilities in children (Cherny et al 1992;Kovas et al 2007b;Petrill et al 1998;Ronald et al 2002) and high reading ability in children and adolescents (Boada et al 2002). Similarly, heritabilities of low ART performance and low reading/spelling ability did not differ significantly from that of the normally distributed measure, as has been found for low mathematics ability in children (Kovas et al 2007a).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The finding that the heritability of high performance in adolescents, for both ART and reading and spelling ability, is of similar magnitude to that found in the population sample, is in line with previous reports for high general cognitive abilities in children (Cherny et al 1992;Kovas et al 2007b;Petrill et al 1998;Ronald et al 2002) and high reading ability in children and adolescents (Boada et al 2002). Similarly, heritabilities of low ART performance and low reading/spelling ability did not differ significantly from that of the normally distributed measure, as has been found for low mathematics ability in children (Kovas et al 2007a).…”
Section: Discussionsupporting
confidence: 89%
“…MacArthur Longitudinal Twin Study (MALTS) Cherny et al 1992; Twins Early Development Study (TEDS) Kovas et al 2007b;MALTS Petrill et al 1998;TEDS Ronald et al 2002) as does the study of low reading and mathematics ability (Kovas et al 2007a, b). Similarly, a study of high reading ability in a sample of 8-18 year olds suggested a continuous distribution of genetic influence (Boada et al 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Van Bergen et al (in press) argue that the most plausible explanation is that early language (verbal IQ) and later reading ability share aetiological factors. The finding that nonverbal IQ was related to later reading and arithmetic skills fits with the generalist genes hypothesis, stating that genes influencing different academic domains and IQ partly overlap (Kovas et al, 2007). The finding that nonverbal IQ was related to later reading and arithmetic skills fits with the generalist genes hypothesis, stating that genes influencing different academic domains and IQ partly overlap (Kovas et al, 2007).…”
Section: Iqmentioning
confidence: 61%
“…In addition, at age 4, FR children who later developed dyslexia were impaired compared with controls on early verbal and nonverbal IQ, whereas the FR children who did not differed only on verbal IQ (van Bergen et al, in press). As is argued, the findings regarding nonverbal IQ are best interpreted within the model of shared aetiological factors, like generalist genes (Kovas et al, 2007). The most plausible interpretation is that the relatively low verbal IQ of the children who go on to develop dyslexia is the consequence of underlying deficits that are also responsible for later reading problems.…”
Section: Discussionmentioning
confidence: 99%
“…In the same sample, reading comprehension was found to be less heritable than all other reading measures, including reading fluency (Kovas, Haworth, Dale, & Plomin, 2007). Our focus on reading comprehension may explain the discrepancy between our heritability estimates for reading achievement and those reported in the literature, which are usually higher (Kovas et al, 2007). Similarly, the present study specifically focused on the enjoyment and self-perceived ability aspect of motivation.…”
Section: Discussionmentioning
confidence: 99%